An anion and small molecule inhibition study of the β-carbonic anhydrase from Staphylococcus aureus. (1st January 2021) - Urbanski, Linda J.; Vullo, Daniela; Parkkila, Seppo; Supuran, Claudiu T.
Abstract: Pathogenic bacteria resistant to most antibiotics, including the methicillin-resistant Staphylococcus aureus (MRSA) represent a serious medical problem. The search for new antiinfectives, possessing a diverse mechanism of action compared to the clinically used antibiotics, has become an attractive research field. S. aureus DNA encodes a β-class carbonic anhydrase, SauBCA. It is a druggable target that can be inhibited by certain aromatic and heterocyclic sulphonamides. Here we investigated inorganic anions and some other small molecules for their inhibition of SauBCA. The halides, nitrite, nitrate, bicarbonate, carbonate, bisulphite, sulphate, stannate, and N, N -diethyldithiocarbamate were submillimolar SauBCA inhibitors with K I s in the range of 0.26 − 0.91 mM. The most effective inhibitors were sulfamide, sulfamate, phenylboronic acid, and phenylarsonic acid with K I s of 7 − 43 µM. Several interesting inhibitors detected here may be considered lead compounds for the development of even more effective derivatives, which should be investigated for their bacteriostatic effects.